1962
DOI: 10.1172/jci104530
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acth, Renin, Angiotensin Ii, and Various Precursors on Biosynthesis of Aldosterone by Adrenal Slices

Abstract: Angiotensin II has been shown to increase the excretion (1) and secretion (2) of aldosterone by normal human subjects, and the secretion of aldosterone by hypophysectomized, nephrectomized dogs (3)(4)(5). In the latter preparation (3), renin, which leads to the liberation of angiotensin in the circulation (6), has been shown to stimulate aldosterone secretion. The present studies were done to determine whether angiotensin and renin can act directly on the adrenal cortex. The slices were minced with scissors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
1
2

Year Published

1963
1963
1992
1992

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(57 citation statements)
references
References 29 publications
2
52
1
2
Order By: Relevance
“…The renin content of kidney tissue correlates well with the thickness of the zona glomerulosa of the adrenal cortex and with the measured aldosterone production rate (3,4). Angiotensin has been shown to stimulate aldosterone production both in man (5,6) and in intact animals (4,7), and it is a powerful stimulus to the biosynthesis of aldosterone in vitro (4,8). Although its role under normal physiological conditions is not clear (7), the renin-angiotensin system has been implicated in the maintenance of certain states of experimentally produced hyperaldosteronism (9), and angiotensin may be an aldosterone-stimulating hormone (ASH).…”
mentioning
confidence: 61%
“…The renin content of kidney tissue correlates well with the thickness of the zona glomerulosa of the adrenal cortex and with the measured aldosterone production rate (3,4). Angiotensin has been shown to stimulate aldosterone production both in man (5,6) and in intact animals (4,7), and it is a powerful stimulus to the biosynthesis of aldosterone in vitro (4,8). Although its role under normal physiological conditions is not clear (7), the renin-angiotensin system has been implicated in the maintenance of certain states of experimentally produced hyperaldosteronism (9), and angiotensin may be an aldosterone-stimulating hormone (ASH).…”
mentioning
confidence: 61%
“…It has been suggested that angiotensin might be the mediator of the natropenic stimulus to aldosterone secretion (11,12,14), and it has been observed that angiotensin acts early in the aldosterone biosynthetic pathway (5). In designing the present study we preferred to make no assumptions as to whether angiotensin is the mediator of the natropenic stimulus to aldosterone secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II (AII),' potassium (K+), and ACTH are the major stimulators of aldosterone synthesis in vitro and in man (1)(2)(3) All three agonists activate the calcium messenger system, however, only All induces the hydrolysis of phosphoinositides and releases intracellular calcium (4)(5)(6). After binding to its receptor, All activates phospholipase C, which induces the formation of diacylglycerol and the release of arachidonic acid (AA) (7).…”
Section: Introductionmentioning
confidence: 99%